(untitled) (Signifiances (Signifying), 2024)
Emojis, small pictographic characters commonly used in electronic messages, have become a global phenomenon. This study utilizes key enactive concepts to demonstrate how emojis reflect the ongoing interplay between technology, language, and culture. A central theme of the analysis is the role of metaphors in justifying the design, use, and interpretation of emojis, illustrating how these symbols originate, evolve, and adapt to the contextual nuances of our environment. The ultimate goal of this study is to enhance our understanding of the evolving meanings of emojis, emphasizing their dynamic nature, and enriching our understanding of their role and interpretation in contemporary human expression and interaction. In this context, emojis emerge as cultural artifacts that are both shaped by and continually shape how we communicate and interact in the digital age. Les émojis, petits caractères pictographiques utilisés couramment dans les messages électroniques, sont devenus un phénomène mondial. Cet article utilise des concepts clés de l’énaction pour démontrer comment les émojis reflètent l’interaction continuelle entre la technologie, le langage et la culture. Un thème central de l’analyse est le rôle des métaphores dans la justification de la conception, de l’utilisation et de l’interprétation des émojis, illustrant comment ces symboles naissent, évoluent et s’adaptent aux nuances contextuelles de notre environnement. Cette étude contribue à mieux comprendre les significations changeantes des émojis, à souligner leur nature dynamique et à enrichir notre compréhension de leur rôle et de leur interprétation dans l’expression et l’interaction humaine contemporaine. Dans ce contexte, les émojis deviennent des artefacts culturels qui sont autant façonnés que qui façonnent continuellement notre manière de communiquer et d’interagir à l’ère numérique.